Effect of milling time on alumina-titania-carbon nanotube by powder metallurgy method - Masri, Mohamad Najmi; Yusoff, Mahani; Nordin, N.N (2018)
The Recent work discovers the evaluation on alumina-titania-carbon nanotube (Al2O3–TiO2–CNT) composite prepared by powder metallurgy method. The properties of Al2O3–TiO2–CNT composite have high hardness, chemical and thermal resistance, wear and corrosion resistance but lacking to low fracture toughness which lead to brittle properties. Hence, CNTwas added to the system due to attractive mechanical properties, low density and high fracture toughness. Elemental powders of Al2O3–TiO2–CNT were milling in low energy ball milling using different milling time at 15, 30, 45 and 60 hours. The peak XRD of TiO2 and CNT become diminished with increasing milling time. The powder that milled at 60 hour possible to has lowest crystallite size and highest internal strain due to finer and homogenous particle size deform during milling.